2019
DOI: 10.1007/s00068-019-01181-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the application of a checklist during trauma resuscitations on ATLS adherence, team performance, and patient-related outcomes: a systematic review

Abstract: Purpose In this systematic literature review, the effects of the application of a checklist during in hospital resuscitation of trauma patients on adherence to the ATLS guidelines, trauma team performance, and patient-related outcomes were integrated. Methods A systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Metaanalyses checklist. The search was performed in Pubmed, Embase, CINAHL, and Cochrane inception till January 2019. Randomized controlled-or controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…One SR [ 28 ] including one study reported this outcome in the adult population. The incidence of one of the ten complications (pneumonia) was slightly higher after the introduction of the checklist (aOR 1.69, 95% CI 1.03–2.80).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…One SR [ 28 ] including one study reported this outcome in the adult population. The incidence of one of the ten complications (pneumonia) was slightly higher after the introduction of the checklist (aOR 1.69, 95% CI 1.03–2.80).…”
Section: Resultsmentioning
confidence: 89%
“…One SR [ 28 ] including one study reported this outcome in 3422 adult trauma patients: incidence of missed injuries did not differ before and implementation of a checklist (aOR 0.62; 95% CI 0.19–2.03; p = 0.437).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…By contrast, p-OHCA accounts for a further 7037 children brought to United States PEDs each year [1]. Variable adherence to resuscitation algorithms is commonly observed and can hinder optimal trauma and CPR care, thus jeopardizing patient outcome and survival [60][61][62][63][64]. In addition to the technical skills of individual rescuers, shared mental non-technical skills at the team level such as SA, collective team interaction patterns, leadership, and dynamic decision-making affect adherence to algorithms and hence the outcome of resuscitation care [22,65].…”
Section: Discussionmentioning
confidence: 99%